Modelling annual scintillation velocity variations of FRB 20201124A. Issue 1 (21st March 2023) - Main, R A; Bethapudi, S; Marthi, V R; Bause, M L; Li, D Z; Lin, H-H; Spitler, L G; Wharton, R S
ABSTRACT: Compact radio sources exhibit scintillation, an interference pattern arising from propagation through inhomogeneous plasma, where scintillation patterns encode the relative distances and velocities of the source, scattering material, and Earth. In previous work, we showed that the scintillation velocity of the repeating fast radio burst (FRB) FRB20201124A could be measured by correlating burst spectrum pairs, with low values of the scintillation velocity and scattering time-scale suggesting scattering nearby the Earth at $\sim$ 0.4 kpc. In this work, we have measured the scintillation velocity at 10 epochs spanning 1 yr, observing an annual variation that strongly implies the screen is within the Milky Way. Modelling the annual variation with a 1D anisotropic or 2D isotropic screen results in a screen distance $d_{ l} = 0.40± 0.04$ or $0.46± 0.06\, $ pc from the Earth, respectively, possibly associated with material outside of the Local Bubble or the edge of the Orion–Eridanus superbubble. Additional measurements particularly at times of low effective velocity will help probe changes in screen properties, and distinguish between screen models. Where scintillation of an FRB originates in its host galaxy or local environment, these techniques could be used to detect orbital motion, and probe the FRB's local ionized environment.